PHILOSOPHY OF VIEWING TOWER AT CIPANAS DAM AREA - Wamenarno, Dwi Wahyu; Handayani, Sri (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2023)
One of the sectors that is progressing and is growing rapidly, especially in Indonesia today is tourism. Tourism has an important role in increasing the income of a region.In terms of employment, the tourism sector can also be a solution to reduce the unemployment problem which is currently rife in various parts of the country.In terms of cultural diversity and natural beauty, Indonesia can become one of the unique tourist destinations in this regard, one of which is Dam Tourism.This study aims to determine that the aesthetics of the building form can be achieved through geometric shapes.Most of the viewing towers that have been built are only concerned with functions, without paying attention to the overall visuals, this is very unfortunate because this viewing tower is one of the most visited building objects when there are visiting events, both from agencies, elementary schools, high schools junior high school, as well as visits from universities, even visits from general visitors.The research method used in this study is descriptive with a qualitative approach, where descriptive qualitative method is a research method based on the philosophy of postpositivism used to examine the condition of natural objects (as opposed to experiments) where the researcher is the key instrument of data collection techniques carried out manually. trigulation (combined), data analysis is inductive/qualitative, and qualitative research results emphasize meaning rather than generalization.The results of the research from the basic concepts of geometric shapes, functionally, the Tower of View in this Rest Area can maximally observe what facilities are in this dam building. Of course, it is supported by the highest elevation of the land on which the Tower of View building stands.